Keterlibatan Ayah dan Pendekatan Neuro-Linguistic Programming dalam Tumbuh Kembang Anak Usia Dini: Studi Literatur - Maghfirah, Rizqa Maulida Syahril (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – The purpose of this study is to examine the role of father involvement in child-rearing and the application of Neuro-Linguistic Programming (NLP) techniques in enhancing communication, as well as supporting the emotional, social, and cognitive development of children. This study aims to understand how NLP techniques can help children build self-confidence, manage emotions, and encourage more effective father involvement in parenting.Method – This study uses a literature review method, which examines 12 relevant studies and literature published between 2010 and 2023. The data is analyzed through content analysis to gather insights on the role of NLP in father-child interactions and child development. Findings – The involvement of fathers in child-rearing is crucial for the emotional, social, and cognitive development of children. The application of NLP techniques, such as anchoring, reframing, and rapport building, enhances communication between fathers and children. These techniques help children manage their emotions, build self-confidence, and view challenges as opportunities for growth. For example, anchoring supports children in creating positive emotional states, while reframing allows them to see challenges more constructively. Research Implications – This research is based on a literature review and does not explore the direct application of NLP in various family contexts. Furthermore, it is important to recognize that child development is influenced by numerous factors beyond NLP, such as socio-economic conditions and culture. This study's limitation lies in its methodological focus on literature without empirical validation through direct father-child experiences. Further research is needed to explore how NLP techniques can be practically applied in diverse family settings and their long-term effects on child development.